Optimal Pricing and Pre-Sale Policies for Perishable Product in an EOQ Inventory Model - Lianxia Zhao; Li Zhang; Jianxin You; Chunyan Duan (IEEE Access)
This paper considers an optimal pricing and pre-sale policy of an EOQ inventory model for perishable products, in which the demand of pre-sale period is dependent on price and pre-sale time, and the demand of spot-sale period is dependent on the price and stock level. Several theoretical results are derived to demonstrate the existence and uniqueness of the solution. For comparison, we also propose a benchmark inventory model in which all the products are to be sold in a spot-sale period, and the optimal policy of pricing and economic order quantity is provided. The numerical experiments are carried out and the sensitivity analysis of the parameters is presented to illustrate the theoretical results for the proposed inventory model, and the comparative analysis of the two models is provided to show if the pre-sale policy is better off the spot-sale policy under some conditions and vice versa.